DEFINITION OF THE TERM CONCEPT IN ENGLISH AND UZBEK - Karimova Dilorom Shavkat (Journal of new century innovations, 2022)
The article deals with the comparative analysis of the verbalization of the concept Word at the lexical level in the English, Russian and Uzbek languages. The analysis of the representation of the concept Word/So’z/Word was carried out on the basis of lexicographic data given in the explanatory dictionaries of the English, Russian and Uzbek languages. The results of the analysis showed that in spite of being one of the universal concepts peculiar to any language and linguaculture, the concept Word has a number of culturally specific features of representation in each of the languages.